Prospecção de metabólitos sanguíneos referenciais para ovinos em distintas categorias - Varanis, Laura Ferrari Monteiro (2018)
The objective of this study was to define reference intervals for energy, protein, mineral and enzymatic metabolic values for sheep of different categories (young - from zero to 12 months, adults - over 12 months, pregnant sheep and lactating ewes. The data used come from several experiments carried out from 2006, in several institutions. Sheep were raised in different management systems (to pasture, semi confinement, total confinement, metabolic cages), all of them being healthy. Data from animals that had any clinical manifestations were discarded. When comparing the ranges defined in the present study with values recommended in the literature, it was possible to observe that several metabolites may present values above the upper limit and / or below the lower limit. This is explained by the data of the literature consulted being international, where the factors race, region, age, management and mainly physiological state may not correspond to the reality of the animals observed here. Each category presents particularities in its physiology, which results in differences in animal metabolism. Therefore, it is possible to conclude that values defined for each animal category should be known, since it presents appropriate metabolic indicators for each of them, so that the interpretation of the metabolic profile is correct.